A comparative analysis of reconstructive crime scene - Emri, Muhamad Fuad; Lau, Chong Luh; Razali, Mohamad Hezri; Idris, Ahmad Norhisyam; Sulaiman, Saiful Aman; M. Idris, Khairulnizam; Abdul Ghani, Muhammad Nasri (UiTM Press, 2025)
In this new technology era, crime scene reconstruction should be enhanced with the latest technology instead of using conventional two-dimensional (2D) approach. This study expands our knowledge of how to employ iPhone LiDAR to speed up the process of gathering crime scene data. With the aim of revolutionising forensic efficiency, this study investigates the potential of iPhone LiDAR in crime scene reconstruction with conventional techniques. In this study, distometer, measuring tape, iPhone 14 Pro Max and Total Station were used for data collection. The objectives include creating a crime scene sketch by hand, converting point clouds data into a 2D drawing, and analysing measurements obtained from various techniques. In this study, Total Station was used to conduct the detail survey of the crime scene. In this study, the distometer was used for baseline measurements while the measuring tape was utilised for short distances measurements. IPhone LiDAR 14 Pro Max, which is equipped with a 3D Scanner App, was used as the proposed approach for data collection. The findings demonstrate that the manual measurements using a distometer and measuring tape are less accurate than LiDAR readings when compared with the readings acquired from the Total Station.